Patterns of DNA methylation changes in elite Eucalyptus clones across contrasting environments - Jacinto Pereira, Wendell; de Castro Rodrigues Pappas, Marília; Camargo Campoe, Otávio [UNESP]; Stape, José Luiz; Grattapaglia, Dario; Joannis Pappas Jr, Georgios (Elsevier, 2020)
Phenotypic plasticity refers to the ability of a single genotype to express distinct phenotypes in response to the environment, a crucial feature for sessile organisms like forest trees, especially in a scenario of global climate change. Several studies show that epigenetic regulation plays an important role in this plastic adaptation response, driving the search for associations between natural epigenetic variation with environmental cues and phenotypic traits based on patterns of cytosine methylation. Clonally propagated trees across variable sites offer a robust system to control for the confounding effect of the background genetic variation among genotypes, allowing the analysis of epigenetic modifications in response to variable environments. In this study we investigated the overall patterns of epigenetic changes by the analysis of the genome-wide DNA methylation status based on high throughput MS-DArT-seq (Methyl Sensitive DArT-seq sequencing) of reduced genome complexity representations. We compared patterns of DNA methylation of biological replicates of leaf and xylem tissue samples of four commercially planted elite Eucalyptus grandis × Eucalyptus urophylla clones and one Eucalyptus urophylla in two contrasting sites in Brazil, and the association of these methylation patterns with the environments and growth traits. DNA sequence reads were mapped against the Eucalyptus grandis reference genome, counting and annotating differentially methylated sites. A total of 90,378 MS-DArT-seq sites were identified, the majority (~70%) located in genes and 10% in transposable elements. The distribution of methylation sites showed extensive variation between the five genotypes and the environments. Sets of methylation sites exclusive to each location were identified for each clone but no consistently shared epigenetic marks for all five clones were found across environments. Multiple correspondence analysis suggests a significant contribution of the genetic background on the distribution of methylation changes. We used a gene-environment association analysis to search for association of methylation patterns with growth traits. A total of 445 methylation sites across all 11 Eucalyptus chromosomes were found significantly associated with one or more of the three measured traits (total height, estimated volume and breast high diameter). The absence of clustered differentially methylated sites is consistent with the fact that complex growth traits are governed by a large number of loci of small effect across the entire genome suggesting that this same pattern will likely hold for what regards epigenetic marks.
Keywords: Epigenetics; MS-DArT-seq; Phenotypic plasticity; TECHS